Statistical Analysis of Student Interest in Physics Education Fkip Jember University 2019-2023 - Utami, Jovica Surya; Putri, Mah Citra Yunia Artika; Pratami, Attica Putri Nurus; Mahardika, I Ketut; Handono, Sri; Ernasari, Ernasari (Peneliti.net, 2023)
This article aims to find out statistics on the interest of Physics Education students at FKIP Jember University from 2019 to 2023. This research approach uses quantitative descriptive because the data process is in the form of numbers and is described in descriptions. Statistics is a science that studies how to plan, collect, analyze and interpret until finally presenting data. The enthusiasm of Jember University FKIP Physics Education students that emerged was generated from questionnaire data which included several questions that had reached the interest questions of Jember University FKIP Physics Education students which resulted in: 1) Interested in Physics Education with a percentage result of 62.35%, 2) Not interested in Physics Education with a percentage result of 37.65%, 3) Students who make Physics Education their first choice with a percentage result of 59.4%, 4) Students who make Physics Education a backup choice with a percentage result of 40.6%, 5) Students who felt that Physics Education met expectations with a percentage result of 62.3%, 6) Students who felt they were in the wrong major in Physics Education with a percentage result of 37.7%. This can be seen from the large percentage of questionnaire results.